Less-Conventional Low-Consumption Galvanic Separated MOSFET-IGBT Gate Drive Supply - Jean Marie Vianney Bikorimana; Alex Van den Bossche (Active and Passive Electronic Components)
A simple half-bridge, galvanic separated power supply which can be short circuit proof is proposed for gate driver local supplies. The supply is made while hacking a common mode type filter as a transformer, as the transformer shows a good insulation, it has a very low parasitic capacitance between primary and secondary coils, and it is cost-effective. Very low standby losses were observed during lab experiments. This makes it compatible with energy efficient drives and solar inverters.